Methods Of Processing The Well Bottom Zone Of The Layer - Azizova Dilorom G’ayratovna (Genius Journals, 2025)
In this article, in order to increase the specificity of extracting Wells, processing of the layer into the extraction zone is carried out at all stages of drilling oil fields in order to restore and increase the filtration properties of the well bottom zone of the layer. In order to restore and increase the filtration properties of the fossil zone of the layer in order to increase the productivity and receptivity of extractive Wells, the types of processing of the layer into the extraction zone are presented at all stages of drilling in oil fields.
Keywords: restoration of filtering properties; exposure to the fossil zone; washing off foam or SFM